2012
DOI: 10.3758/s13414-012-0395-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal characteristics of overt attentional behavior during category learning

Abstract: Many theories of category learning incorporate mechanisms for selective attention, typically implemented as attention weights that change on a trial-by-trial basis. This is because there is relatively little data on within-trial changes in attention. We used eye tracking and mouse tracking as finegrained measures of attention in three complex visual categorization tasks to investigate temporal patterns in overt attentional behavior within individual categorization decisions. In Experiments 1 and 2, we recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Some studies have utilized eye movements to tap into mental states such as confusion and concentration (Griffiths, Marshall, & Richens, 1984;Victor, Harbluk, & Engström, 2005), arousal (Subramanian et al, 2010;Woods, Beecher, & Ris, 1978), or deception (Kuhn & Tatler, 2005). Eye movements can also be utilized as a measure of learning capacity in category learning and feature learning (e.g., Chen, Meier, Blair, Watson, & Wood, 2013;Rehder & Hoffman, 2005) and expertise (e.g., Bertram, Helle, Kaakinen, & Svedström, 2013;Jarodzka, Scheiter, Gerjets, & Van Gog, 2010;Vogt & Magnussen, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have utilized eye movements to tap into mental states such as confusion and concentration (Griffiths, Marshall, & Richens, 1984;Victor, Harbluk, & Engström, 2005), arousal (Subramanian et al, 2010;Woods, Beecher, & Ris, 1978), or deception (Kuhn & Tatler, 2005). Eye movements can also be utilized as a measure of learning capacity in category learning and feature learning (e.g., Chen, Meier, Blair, Watson, & Wood, 2013;Rehder & Hoffman, 2005) and expertise (e.g., Bertram, Helle, Kaakinen, & Svedström, 2013;Jarodzka, Scheiter, Gerjets, & Van Gog, 2010;Vogt & Magnussen, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…There are at least two possible explanations for longer fixations in younger children. Firstly, it has been proposed that fixation durations are directly related to the difficulty of cognitive processes such as information extraction (Chen et al, 2013;Groner & Groner, 1989;Just & Carpenter, 1980) or recall in memory tasks . Additionally, it has been shown that infants who exhibit shorter looking times are faster in the processing of visual stimuli when compared with same-aged infants with longer looking times (Colombo et al, 1991;Sigman et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…One fundamental assumption of reward and reinforcement learning theories is that dimension attention (also referred to as feature or cue attention) corresponds to how well a dimension predicts rewards or decision outcomes (Sutton & Barto, 1998). Indeed, in standard category-learning tasks, participants shift attention to those stimulus features that reliably predict category membership (e.g., Blair, Watson, & Meier, 2009;Chen, Meier, Blair, Watson, & Wood, 2013;Matsuka & Corter, 2008;Rehder & Hoffman, 2005a, 2005b. According to a recent review by Le Pelley et al (2016), however, dimension attention also depends on the value of the predicted outcome.…”
Section: Reward Feature Attention and Rule-based Strategiesmentioning
confidence: 99%